Assessment of a Healthy Lifestyle and Quality of Life of Men and Women in Modern Society Based on SF-36 - Krutsevich, Tatiana; Trachuk, Sergii; Ivanik, Oksana; Panhelova, Natalia; Brychuk, Mariia; Kedrych, Halyna (Physical Education Theory and Methodology, 2021)
Quality of life (QL) is defined as the subjective perception of one’s own well-being in a socio-cultural context, the satisfaction of one’s desires and the achievement of an ideal level of well-being. Quality of life is related to health (HRQOL), refers to the functioning and well-being in the physical, mental and social dimensions of life. Research purpose: to analyze the main factors of quality of life of male and female population in modern Ukrainian society. Material and Methods. 482 men and women aged 20-60 took part in sociological research. The following research methods were used to solve the problemsset in the work: analysis and processing of special literature and data from the Internet; pedagogical observation; questionnaires (SF36); methods of mathematical statistics. Results. The results of their own research show that the male population had a better quality of life on all scales of the SF-36 questionnaire compared to women (p <0.05). Respondents under the age of 20-29 had indicators of quality of life above average on the scales of physical and role physical functioning; pain in this age group did not have a significant impact on quality of life. The general state of health was assessed above the average level by respondents aged 20-29 and 30-39, regardless of gender, they were characterized by high scales of social activity and viability. Conclusions. It is established that the indicator General health is a system-forming factor of quality of life for men and women in terms of the number of correlations. The obtained results allowed to determine the expediency and speed of implementation of preventive measures for men and women depending on the content of certain scales. Decreased overall health (GH) in men and women after the age of 50 significantly affects their quality of life, as evidenced by the large number of significant correlation coefficients. In women over 50 years of age, there is a sharp decrease in RP (role functioning due to physical condition) to 46 points, vital activity (VT) to 50 points, role functioning (due to emotional state) (RE) to 53 points. In men at this age, role functioning increases to 90 points, and social functioning (SF) to 89 points, which may indicate an uneven distribution of family and social functions in the lives of people of different sexes, overloading women with household chores, which prevents them from spending free time, affects the emotional state.